Long-distance conveyance of California obsidian at the Hayhurst lithic cache site (34ML168) in Oklahoma. (3rd July 2018) - Dolan, Sean G.; Shackley, M. Steven; Wyckoff, Don G.; Skinner, Craig E.
Abstract : A piece of obsidian was found during excavations of a possible Middle Holocene Calf Creek biface cache at site 34ML168 in Oklahoma. Energy dispersive X-ray fluorescence analysis of the obsidian flake shows that the source material derives from Glass Mountain in California. This is the first instance of California obsidian in this region. However, most intriguing is that Glass Mountain erupted thousands of years after the presumed Calf Creek artifacts were made. By examining the depositional history and lithic technology of the cache, and source provenance of the obsidian, we discuss the significance of this find and present possible scenarios regarding the long-distance conveyance of the obsidian artifact. This study complements other archaeological cases where the use of geochemical sourcing connects people, places, and things of unexpected distances across ancient North America.